The Influence CSR Disclosure on Profitability of Sri-Kehati Indexed Companies with Institutional Ownership as Moderator - Febryanti, Ajeng Winda; Ni Made Dwi Ratnadi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to empirically prove the effect of CSR disclosure on profitability and the ability of institutional ownership as a moderating variable on that relationship. The research employed a quantitative method with regression moderation analysis, facilitated by the SPSS analysis tool. The research sample consisted of 55 companies with secondary data. The results showed that CSR disclosure had an effect on the profitability of companies indexed by Sri-Kehati. Institutional ownership can moderate the effect of CSR disclosure on the profitability of companies indexed by Sri-Kehati. This result of this study prove empirically that the higher level of CSR disclosure, the more effective management will be managing its assets. The greater proportion of institutional ownership, the greater the pressure on management to disclose its social responsibility comprehensively.